The impact of Mass customization In Quality costs - خولة حسين حمدان; حسين كريم محمد الشمري (Journal of Madenat Alelem University College, 2017)
This study aims to determine the relationship between Mass customization and quality costs in economic units , And a statement of its impact on the rationalization of costs and good finish failure costs (internal and external) And the main findings of the study (rely on a system wide modern means recommended production that will help manage the economic units to production as the customer desires) The main conclusion of the study (the need to rely on automated production system and high-tech factories will cost to cancel all internal and external failure costs).